FACTORS MILITATING AGAINST PUBLIC HEALTH FINANCING IN NIGERIA: AN EMPIRICAL REVIEW - Tayo-Ladega, Oluwadamisi; Abdullahi, Taye Mohammed; Islam, K. M. Anwarul (American International Journal of Multidisciplinary Scientific Research, 2021)
An effective and quality health care service is one of the fundamental visions of every government to its citizenry because it is only the healthy people that can be governed and will value developmental projects. Citizens having access to quality health services translate to significant development in modern society. Therefore, the provision of adequate funds for the sector is essential. However, the Nigeria health care sector is currently confronted with colossal issues that should be surmounted to enhance effective and quality health care delivery to the citizens. This study is rooted in the evidence of appropriate works of literature in the financing of public health care services in Nigeria. From the extant works of the literature surveyed, it was revealed that public health care services in Nigeria are financed by revenue that is accrued from public tax, funding from donors, health insurance, and direct payments made by individuals. Furthermore, public health service is mostly financed by direct payments made by individuals with the government. The most perturbing issues combating public health care financing are direct payments made by individuals, poor government funding, health care policy defects in implementation, and corruption scandals. On this note, the study recommended an effective and robust government funding of public health, implementation of sound health care policies, efficient monitoring of public funds utilization, and discouraging foreign medical trips.JEL Classification Codes: A19, B10, B25, C10, C53.